Efficacy of Intermittent, Oral Famciclovir Prophylaxis for Bortezomib-Induced Herpes Zoster in Multiple Myeloma Patients - Zheng, Gaofeng; Guan, Fangshu; Han, Xiaoyan; Yang, Li; Zhao, Yi; Yang, Yang; Zhang, Enfang; He, Jingsong; He, Donghua; Wu, Wenjun; Huang, He; Cai, Zhen (Frontiers in Oncology, 2022)
Objective: To explore the efficacy and safety of intermittent, oral famciclovir prophylaxis for bortezomib-induced herpes zoster in multiple myeloma patients. Method: We retrospectively analyzed the incidence of bortezomib treatment-related varicella-zoster virus reactivation in 719 newly-diagnosed multiple myeloma patients receiving intermittent oral famciclovir prophylaxis, continuous oral acyclovir prophylaxis or no prophylaxis. The definition of intermittent oral famciclovir prophylaxis was oral famciclovir at a dose of 250mg twice daily for 9 days after finishing the last dose of bortezomib therapy every cycle. Age, gender, stage per the International Staging System, type of M protein, baseline of absolute lymphocyte count, absolute neutrophil count, and absolute monocyte count were analyzed to find the potential factors that could predispose to herpes zoster infections. Results: Varicella-zoster virus infection occurred in 96 patients (13.4%) during bortezomib treatment. The incidence of herpes zoster was significantly higher in the no-prophylaxis group compared with the prophylaxis group (22.9% vs 8.2% P<0.001), while the rate was similar between the intermittent oral famciclovir group and the continuous oral acyclovir group (8.4% vs 7.9% P=0.835). Hepatic and renal toxicity were observed in 12% and 2.8% of the patient respectively in the intermittent famciclovir group, which was similar in the continuous acyclovir group (18.1% and 4.2%). The prophylactic use of antiviral agents is a predictive factor for varicella-zoster virus reactivation. Conclusion: Intermittent famciclovir prophylaxis is effective and safe in preventing herpes zoster development and can markedly reduce the duration of oral medicine treatment compared with continuous acyclovir prophylaxis.